The effectiveness of a proposed training program for developing the creative teaching skills of science teachers in Zintaan city and its impact on the full engagement of learners in the learning process. (Journal of Human Sciences, 2021)
The aim of the research is to: identify the effectiveness of a proposed training program for developing creative teaching skills for science teachers in zintaan ,, and to find out whether there are statistically control and experimental group, for the development of creative teaching, and to find out whether there are statistically significant differences between the members of the control and experimental group, for the development of creative teaching skills, and engaging in learning of science teachers, the two researchers prepared: a training program and two note cards to develop creative teaching skills and engaging in learning of science teachers, the research included a sample of (30), including (15) female teachers in the experimental group, (15) female teachers control group they were chosen at random, the two researchers used the quasi-experimental method, the results of the research found the following: the effectiveness of a proposed program for developing creative teaching skills for science teachers and its impact on achieving full engaging in learning, there are statistically significant differences between the mean scores of the experimental group members in tribal measurement, and the average of their scores in the dimensional measurement on the creative teaching skills note card, in favor of telemetry, there are statistically significant differences between the mean scores of the experimental group members, and the average scores of the control group members in the post-measurement on a note card for creative teaching skills, for the benefit of the experimental, there are statistically significant differences between the mean scores of the experimental group members, in the tribal measurement, and the average of their score in the post-measurement on the learning engagement note card, in favor of telemetry, there are statistically significant differences between the mean scores of the experimental group members and the control group members' mean scores in the.post measurement on the learning engagement note card for the benefit of the experimental